Linagliptin improves endothelial function in patients with type 2 diabetes: A randomized study of linagliptin effectiveness on endothelial function. Issue 3 (21st November 2016) - Shigiyama, Fumika; Kumashiro, Naoki; Miyagi, Masahiko; Iga, Ryo; Kobayashi, Yuka; Kanda, Eiichiro; Uchino, Hiroshi; Hirose, Takahisa
Abstract: Aims/Introduction: The present multicenter, prospective, controlled, open and randomized three‐arm parallel study was designed to compare the effects of linagliptin with those of metformin on endothelial function. Materials and Methods: Type 2 diabetes patients treated with 750 mg of metformin (hemoglobin A1c ≥6.0% and <8.0%, n = 96) were randomized to continue metformin 750 mg/day (control group, n = 29), metformin at 1, 500 mg/day (metformin group, n = 26) and metformin 750 mg/day supplemented with linagliptin 5 mg/day (linagliptin add‐on group, n = 29) and treated for 16 weeks. Vascular endothelial function was evaluated by flow‐mediated dilation. The primary end‐point was changes in flow‐mediated dilation at 16 weeks relative to baseline. Results: Linagliptin significantly improved flow‐mediated dilation from baseline (4.9 ± 2.7%) to 16 weeks (6.3 ± 2.7%, P < 0.05), whereas the other groups did not show any changes. Hemoglobin A1c at 16 weeks was significantly lower in the metformin and linagliptin add‐on groups compared with the control (6.6 ± 0.6%, 6.5 ± 0.5% and 7.0 ± 0.6%, respectively). Single and multiple regression analyses showed that apolipoprotein B correlated significantly with change in flow‐mediated dilation, and apolipoprotein B was decreased only in the linagliptin add‐on group (–6.0 ± 11.3 mg/dL, P < 0.01). Conclusions: Linagliptin for 16 weeks improved endothelial function with a modest improvement in glycemic control. This effect was mediated, at least in part, by reduction in apolipoprotein B. Linagliptin has a protective role on endothelial function in patients with type 2 diabetes with moderate hyperglycemia. Abstract : Linagliptin for 16 weeks improved endothelial function with a modest improvement in glycemic control. This effect was mediated, at least in part, by reduction in apolipoprotein B. Linagliptin has a protective role on endothelial function in patients with type 2 diabetes with moderate hyperglycemia.